Ketimpangan Pembangunan Antarwilayah Pengembangan di Provinsi Papua Barat - Ahmad Raafi’i; Dedi Budiman Hakim; Eka Intan Kumala Putri (P4W LPPM IPB, 2018)
Regional-based development aims to minimize the disparity between regions. Local government of West Papua province divides its region into three development regions (WP), namely (1) Teluk Bintuni, Manokwari, and Teluk Wondama; (2) Maybrat, Raja Ampat, Sorong Regency, Sorong Municipality, South Sorong, and Tambrauw; (3) Fakfak and Kaimana. Each development region has different characteristics from each other. These differences include regional typology (coastal and mountainous), population (under 50 thousand inhabitants, 50-100 thousand inhabitants, and above 100 thousand inhabitants), and administrative status (old districts and new autonomous regions). The purpose of this research is to analyze local typologies and the factors that affect the disparity between development regions in West Papua province by using panel data regression. Analysis technique used are local typologies, Theil Index and panel data regression. Research results show that there are no regions that are dominant in the first quadrant (advanced) and fourth quadrant (underdeveloped) of Klassen typology. Theil Index value, which represents disparity, shows an increasing trend. Variables that affect positively to the Theil Index are length of road, locally-generated revenue, dummy on the absence of the city, dummy on ethnic region, and average expenditure per capita. Meanwhile variables that affect negatively and significantly to the Theil Index are the share of natural resources and dummy on the absence of new autonomous regions.